2023
DOI: 10.3899/jrheum.2023-0742
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough COVID-19 After Tixagevimab/Cilgavimab Among Patients With Systemic Autoimmune Rheumatic Diseases

Yumeko Kawano,
Xiaosong Wang,
Naomi J. Patel
et al.

Abstract: ObjectiveTo determine the incidence and baseline factors associated with breakthrough COVID-19 after pre-exposure prophylaxis (PrEP) with tixagevimab/cilgavimab among patients with systemic autoimmune rheumatic diseases (SARDs).MethodsWe performed a retrospective cohort study among patients with SARDs who received tixagevimab/cilgavimab between January 2, 2022 and November 16, 2022. The primary outcome was breakthrough COVID-19 after tixagevimab/cilgavimab. We performed multivariable Cox regression models adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…Similarly, in a retrospective cohort study of 400 rituximab (RTX)-treated patients in the UK, Yusof et al reported that whereas one-third of the cohort experienced breakthrough COVID-19, only a small proportion of patients experienced severe COVID-19. 8 These findings in the current Kawano et al study 7 and the recent Yusof et al 8 study are in stark contrast to those of numerous other studies throughout the pandemic that demonstrated a strong association between severe COVID-19 and B cell-depleting therapies, throughout all periods of the pandemic. 5 The reasons for these varying outcomes in terms of risk of severe COVID-19 in patients with B cell depletion remain unclear.…”
Section: Editorialcontrasting
confidence: 79%
See 2 more Smart Citations
“…Similarly, in a retrospective cohort study of 400 rituximab (RTX)-treated patients in the UK, Yusof et al reported that whereas one-third of the cohort experienced breakthrough COVID-19, only a small proportion of patients experienced severe COVID-19. 8 These findings in the current Kawano et al study 7 and the recent Yusof et al 8 study are in stark contrast to those of numerous other studies throughout the pandemic that demonstrated a strong association between severe COVID-19 and B cell-depleting therapies, throughout all periods of the pandemic. 5 The reasons for these varying outcomes in terms of risk of severe COVID-19 in patients with B cell depletion remain unclear.…”
Section: Editorialcontrasting
confidence: 79%
“…In this issue of The Journal of Rheumatology, Kawano et al report outcomes of breakthrough COVID-19 in patients with systemic rheumatic disease after receipt of tixagevimab/ cilgavimab and are the first to report this experience over nearly the entire approval period of the product, collecting cases through November 2022. 7 Out of 444 patients, almost one-fifth experienced breakthrough COVID-19 over 2637.6 person-months of follow-up with mostly favorable outcomes. Only 7 patients were hospitalized and 1 died.…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation